An Evaluation of the Social Economic Assessment Toolbox (SEAT) Implementation on Stakeholder Relationships and Community Development in South Africa: A Case Study of Rustenburg Platinum Mine in South Africa - Kapisha, Besa (2008)
The information presented in this report is an outcome of the application of the Socio-Economic Assessment Toolbox (SEAT) to Rustenburg Platinum Mine (RPMR). SEAT was designed to assist Anglo American Group of companies identify and manage their social and economic impacts, both positive and negative. The project investigated the impacts achieved through the implementation of SEAT. The research aimed to collect and analyse data to determine whether the mine meets its sustainable development objectives by contributing to economic sustainable development, identifying major impacts and managing them.